Prognostic utility of early systolic lengthening by speckle tracking echocardiography in patients with type 2 diabetes. (25th November 2020) - Brainin, P; Jensen, M.T; Biering-Soerensen, T; Moegelvang, R; Fritz-Hansen, T; Vilsboell, T; Rossing, P; Joergensen, P.G
Abstract: Background: Early systolic lengthening (ESL) has recently recognized as a predictor of cardiovascular events in patients with myocardial ischemia. Our aim was to evaluate the prognostic value of ESL in patients with type 2 diabetes. Methods: In this prospective study we conducted speckle tracking examinations in 743 patients with type 2 diabetes (62% male; age 63±10 years; diabetes duration 11 [5, 17] years). Patients were free from interventricular conduction disturbances, atrial fibrillation, heart failure and ischemic heart disease at study inclusion. We assessed the ESL index, defined as: (−100 x [peak positive systolic strain / global longitudinal strain (GLS)]), and duration of ESL, defined as time from onset of QRS complex on the electrocardiogram to time of peak positive systolic strain. Measurements were averaged from 18 myocardial segments. Results: During the median follow-up time of 4.8 years [IQR 4, 5.3 years], 93 (13%) patients experienced major adverse cardiovascular events (MACE), a composite of incident heart failure, myocardial infarction and cardiovascular death. Because GLS modified the association with MACE (P interaction <0.05), the population was stratified by the median GLS value (low >−15% and high ≤−15%). In patients with low GLS, the ESL index (HR 1.47 per 1% increase [1.12 to 1.93], P=0.005) and ESL duration (HR 1.73 per 1ms increase [1.10 to 2.72], P=0.017) were associated with MACE. Both associations remained significant in multivariable models adjusted for clinical, echocardiographic and speckle tracking measurements (Figure). No associations were found in patients with high GLS (Figure). Conclusion: Assessment of ESL yields novel and independent prognostic information on major adverse cardiovascular events in patients with diabetes type 2 and reduced longitudinal strain. Funding Acknowledgement: Type of funding source: None